Pengaruh Perubahan Suku Bunga, Nilai Tukar, Pertumbuhan Ekonomi, dan Harga Minyak Terhadap Return Saham Sektor Transportasi dan Logistik Tahun 2006-2024 - Fajar Andrianto; Ahsan Sumantika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of changes in interest rates, exchange rates, economic growth, and world oil prices on stock returns in the transportation and logistics sector in Indonesia during the period 2006–2024. This sector was chosen because it is highly vulnerable to fluctuations in macroeconomic factors that have a direct impact on companies' operating costs and financial performance. The method used is multiple linear regression with an annual panel data approach, using a sample of transportation and logistics companies listed on the Indonesia Stock Exchange. The independent variables include changes in interest rates, exchange rates, economic growth, and oil prices, while the dependent variable is stock returns. The results show that, partially, only changes in interest rates have a significant negative effect on stock returns. Conversely, exchange rates, economic growth, and oil prices have no statistically significant effect. Simultaneously, these four variables also show no significant effect on stock returns. This study makes a new contribution through the use of a long observation period and a focus on the transportation and logistics sector, thereby providing a deeper understanding of this sector's sensitivity to macroeconomic conditions.